Is antitumor Pt(IV) complex containing two axial lonidamine ligands a true dual- or multi-action prodrug? - Kasparkova, Jana; Kostrhunova, Hana; Novohradsky, Vojtech; Ma, Lili; Zhu, Guangyu; Milaeva, Elena R; Shtill, Alexender A; Vinck, Robin; Gasser, Gilles; Brabec, Viktor; Nazarov, Alexey A (Metallomics, 2022)
This work studied the mechanism of action of a Pt(IV) complex 2 bearing two axial lonidamine ligands, which are selective inhibitors of aerobic glycolysis. The presence of two lonidamine ligands in 2 compared to the parent Pt(II) complex increased its antiproliferative activity, cellular accumulation, and changed its cell cycle profile and mechanism of cell death. In 3D cell culture, 2 showed exceptional antiproliferative activity with IC50 values as low as 1.6 μM in MCF7 cells. The study on the influence of the lonidamine ligands in the Pt complex on glycolysis showed only low potency of ligands to affect metabolic processes in cancer cells, making the investigated complex, not a dual- or multi-action prodrug. However, the Pt(IV) prodrug effectively delivers the cytotoxic Pt(II) complex into cancer cells.
Keywords: Cell Line, Tumor; indazoly; protinádorové látky; Antineoplastic Agents; Indazoles; medicinal inorganic chemistry, metals in medicine, Pt(IV) complexes; ligandy; lonidamine; nádorové buněčné linie; Prodrugs; prekurzory léčiv; Ligands; bioinorganic chemistry